Dietary specificity and overlap in endorheic river fishes: How do native and nonnative species compare?. Issue 2 (23rd June 2020) - Minder, Mario; Arsenault, Emily R.; Erdenee, Bolortsetseg; Pyron, Mark
Abstract: The introduction of nonnative species is one of the most critical problems facing freshwater systems today. The rivers of the Great Basin (USA) have been particularly imperilled by nonnative species introductions and represent a valuable location to study the dietary trends of native and nonnative fishes in isolated, endorheic systems. We collected fish from 23 sites, spanning three Great Basin watersheds (Carson, Humboldt and Bear Rivers) and two elevation categories (upland and lowland). Only a single species (speckled dace Rhinichthys osculus ) occurred in both elevation zones. Diet item analyses of over 500 fish stomachs indicated significant dietary overlaps between native and nonnative fishes and detailed dietary selectivity for all species. This finding, along with the low species diversity observed in the region, suggests low dietary niche diversity, which could have the potential to amplify the competitive impacts of nonnatives on native species. In upland sites, nonnative trouts were the dominant invaders, while in lowland sites warm‐water nonnatives were prevalent. The management implications we recommend based on our results urge for continued monitoring of water temperature and species occurrences to predict if dietary overlaps observed in this study are likely to change in the future. Significance Statement: The Great Basin is an ideal endorheic region to study dietary trends in native and nonnative fishes. These trends are important in predicting competitive interactions among fishes. By looking at the diets of fishes within this region we were able to identify multiple significant overlaps among native and nonnative fishes. These results represent a baseline for future studies in the region as well as being comparable to other regions with similar invasive/native overlaps.